Rail Transport Delay and Its Effects on the Perceived Importance of a Real-Time Information - Rezapour, Mahdi; Ferraro, F. Richard (Frontiers in Psychology, 2021)
The impact of various psychological feelings that the commuters might experience due to the shortcoming of a public transport is a major concern for public transport users, and policy makers. Those public transport shortcomings would be translated to the commuters in terms of various negative psychological feelings, which would consequently tarnish the perceived quality of the public transport in terms of its characteristics, e.g. the perceived quality of the passengers’ information system (PIS). The delay has often been defined as difference between real arrival of a transport and scheduled arrival of a transport based on PIS. The main question this study seeks to answer is how passengers view the PIS while undergoing various psychological negative impacts due to the transport delay? That is especially important when the PIS is not precise. Previous studies on the importance of real-time information mainly focus on the impact of PIS on the satisfaction of the commuters, or the reliability of the public transport. However, they barely consider the negative psychological impacts that the delay might have on commuters, and how those negative feelings might be aggravated by providing inaccurate information for the commuters. The proposed study is based on completed instruments by 396 passengers who were waiting for a notorious rail transport in Malaysia: the rail transport was experiencing frequent long delay due to various mechanical malfunctions. In addition, the PIS provided for the passengers were mainly imprecise, and was updated regularly.